Combination pharmacotherapy for the treatment of neuropathic pain in adults: systematic review and meta-analysis. Issue 2 (19th May 2022) - Balanaser, Marielle; Carley, Meg; Baron, Ralf; Finnerup, Nanna B.; Moore, R. Andrew; Rowbotham, Michael C.; Chaparro, Luis E.; Gilron, Ian
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Neuropathic pain causes substantial morbidity and healthcare utilization. Monotherapy with antidepressants or anticonvulsants often fails to provide relief. Combining different drugs sometimes provides improved analgesia and/or tolerability. More than half of patients receive 2 or more analgesics, and combination trials continue to emerge. This review comprehensively searched CENTRAL, MEDLINE, and EMBASE for relevant trials. Included studies are double-blind randomized controlled trials evaluating combinations of 2 or more drugs vs placebo or at least one monotherapy in adults with neuropathic pain. Outcomes included measures of efficacy and adverse effects. Risk of bias was assessed. Meta-analyses compared combination to monotherapy wherever 2 or more similar studies were available. Forty studies (4741 participants) were included. Studies were heterogenous with respect to various characteristics, including dose titration methods and administration (ie, simultaneous vs sequential) of the combination. Few combinations involved a nonsedating drug, and several methodological problems were identified. For opioid–antidepressant, opioid–gabapentinoid, and gabapentinoid–antidepressant combinations, meta-analyses failed to demonstrate superiority over both monotherapies. In general, adverse event profiles were not substantially different for combination therapy compared with monotherapy. Despite widespread use and a growing number of trials, convincing evidence has not yet emerged to suggest superiority of any combination over its respective monotherapies. Therefore, implementing combination therapy—as second- or third-line treatment—in situations where monotherapy is insufficient, should involve closely monitored individual dosing trials to confirm safety and overall added benefit. Further research is needed, including trials of combinations involving nonsedating agents, and to identify clinical settings and specific combinations that safely provide added benefit.